Pemanfaatan Eco Enzyme Sebagai Bahan Aktif Natural Anti Mikroba untuk Pembuatan Produk Sabun dalam Mengatasi Miliaria pada Bayi - Anik Latifah; Retno Setyo Iswati; Desta Ayu Cahya Rosyida; Annah Hubaedah (LPPM STIKES Guna Bangsa Yogyakarta, 2022)
Indonesia is a country that is famous for its cultural diversity and is well known for the wealth of plants that are useful as medicine. In Indonesia, many types of spices are easy to find and grow wild in gardens and yards. Alternative medicine is known as complementary therapy. Complementary therapy as a development of traditional therapy and there is integrated with modern therapy that affects the harmony of individuals from biological, psychological, and spiritual aspects. Complementary therapy aims to improve the function of the body's systems, especially the immune and defense systems. There are many types of methods in this complementary therapy. The risk of the effects of chemical drugs can be reduced more. Therefore, many of our people are more inclined to seek treatment for alternative herbal treatments, which of course are more natural and safer. Community Service Method with the workshop method, which is an activity based on behavior change in community groups with the theme